PEPSUI, a Psychoeducational Program for the Management of Suicidal Patients: A Qualitative Study From a Randomized Controlled Trial - Henrion, Audrey; Courtet, Philippe; Arpon-Brand, Véronique; Lafrancesca, Audrey; Lacourt, Laetitia; Jaussent, Isabelle; Guillaume, Sébastien; Olié, Emilie; Ducasse, Déborah (Frontiers in Psychiatry, 2020)
BACKGROUND: Suicide prevention after a recent suicide attempt remains a major issue for clinicians. As psychoeducation-based interventions are strongly recommended for patients with severe or chronic disorders and poor adherence, we developed the first French program of suicide psychoeducation (PEPSUI). METHODS: We started a large multicenter randomized controlled trial in outpatients who attempted suicide in the last year (i.e. current suicidal behavior disorder) to assess the feasibility, acceptability, and effectiveness of a 10-week psychoeducational program (PEPSUI group: scientific information on suicidal behavior, and third-wave cognitive behavioral therapies) compared with a 10-week relaxation program (control condition), in a naturalistic setting. Here, we present the qualitative part of this study. Participants in both groups completed a narrative interview with questions on their general impressions about the therapy process and outcomes, specific areas of change in their life since inclusion, and knowledge and perceptions about suicide and mental health services. Interviews were audiotaped, transcribed, and coded using inductive and deductive thematic analysis with a constant comparative approach. Participants were consecutively included until data saturation. RESULTS: The interviews of 18 patients (n=10 in the PEPSUI group, and n=8 in the relaxation group) were analyzed. Qualitative analyses revealed some common points, and many differences between groups that are relevant for suicide prevention. Patients in both groups were satisfied with the programs. Group modality and therapeutic alliance with the instructors were considered useful in both groups. Participation was related to improved perception of mental health units (particularly in the PEPSUI group). Both groups reported the acquisition of stress management skills and distress tolerance. Relaxation was an easy way to survive stress. Conversely, the PEPSUI program had deeper implications for daily life through effective positioning towards internal events (thoughts and emotions) as a consequence of mindfulness-derived practices, enhancement of value-based commitments, improvement of the meaning in life and internal locus of control, increased contact with the present moment, use of a matrix (a decision-making tool), and acquisition of scientific knowledge on suicidal behavior. CONCLUSION: Through specific processes for targeting suicidal risk and reducing the stigma, the PEPSUI program may represent a promising intervention for suicide prevention.